Alcohol dehydrogenase 1C (ADH1C) polymorphism is significantly associated with kidney function status in Nusa Tenggara Timur ethnicity: A cross-sectional study - Budiatri Retno Noormaningrum; Yudha Nurhantari; Suhartini Suhartini; Tri Ratnaningsih; Maria Agnes Etty Dedy (Journal of Community Empowerment for Health, 2021)
Excessive alcohol consumption is harmful to many human organs, but the association with kidney function is still controversial. The disagreement in findings might be caused by ADH1C polymorphism's influence on alcohol metabolism rate. This study aims to determine the correlation between ADH1C polymorphism and kidney function status in Nusa Tenggara Timur (NTT) ethnicity, a population with highly prevalent alcohol consumption in Indonesia. We conducted a cross-sectional study of 76 subjects, who are natives of NTT, Indonesia. The genotyping of extracted DNA for ADH1C was done by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using restriction endonuclease SspI. Kidney function status was defined by serum urea level and estimated glomerular filtration rate (eGFR) that had been categorized according to percentiles. The correlation with the ADH1C allele was analyzed using chi-square tests. The genotype of ADH1C in NTT ethnicity was ADH1C*1/*2 (51.3%), ADH1C*2/*2 (47.4%), and ADH1C*1/*1 (1.3%). The results showed that the population had the ADH1C*2 (73.03%) and the ADH1C*1 (26.97%) allele. There was a significant association between ADH1C polymorphism and eGFR among NTT ethnicity (p=0.005) when eGFR was analyzed at the 25th percentile (74.75 mL/minute/1.73m2). However, we found no associations when eGFR was analyzed at 50th (p=0.571) and 75th (p=0.335) percentiles. The odds ratio shows that having the ADH1C*1/*2 genotype escalates the probability of declining eGFR 6.620 times compared to ADH1C*2/*2 (95% CI: 1.539-28.478), after adjusted for smoking behavior. We found no association between ADH1C polymorphism and serum urea level (p=0.123, 0.421, and 0.335). The majority of NTT ethnicity have the ADH1C*1/*2 genotype. Populations with ADH1C*1/*2 have higher odds ratio for eGFR below 74.75 mL/minute/1.73m2 than those with ADH1C*2/*2 genotype. There was no association between ADH1C polymorphism and serum urea levels.